Theatrum musicum longe amplissimum 1571 - Phalèse, Pierre 1510-1577 (Minkoff, 2002)
Contains music, in French tablature, for 1 or 2 lutes, some arranged from vocal works, by Clemens non Papa, Crecquillon, O. Lasso, Kargel, Neusidler, Paulus Baronus, Paladino, Francesco da Milano, Morlaye, Giovanni Maria da Crema, R. Viola, Melchior, Sermisy, Mittantier, Sandrin, Certon, Villiers, Wismes, Pathie, Abran, Lupus (or Cadéac), Verius, Perissone Cambio, Donato, Ferrabosco d'après, Berchem, Verdelot, Rore, Arcadelt, Lupi Second, Bakfark, Gascongue, Jachet, Josquin Desprez, Barbetta, Le Roy & Janequin.